2016
DOI: 10.1038/srep35034
|View full text |Cite
|
Sign up to set email alerts
|

Effect of adding nanometre-sized heterogeneities on the structural dynamics and the excess wing of a molecular glass former

Abstract: We present the relaxation dynamics of glass-forming glycerol mixed with 1.1 nm sized polyhedral oligomeric silsesquioxane (POSS) molecules using dielectric spectroscopy (DS) and two different neutron scattering (NS) techniques. Both, the reorientational dynamics as measured by DS and the density fluctuations detected by NS reveal a broadening of the α relaxation when POSS molecules are added. Moreover, we find a significant slowing down of the α-relaxation time. These effects are in accord with the heterogenei… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
18
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 14 publications
(18 citation statements)
references
References 63 publications
0
18
0
Order By: Relevance
“…We also believe that this is the first time β JG relaxation has been identified from neutron scattering data, although Sperl previously proposed a Cole-Cole form for susceptibilities that accounted for dynamics observed over a similar lengthscale and time scale in optical Kerr effect data. 61 We note also that, very shortly after the first posting of a portion of this work, 62 Gupta et al 63 also showed that β JG relaxation could be obtained from EINS.…”
Section: Discussionmentioning
confidence: 59%
“…We also believe that this is the first time β JG relaxation has been identified from neutron scattering data, although Sperl previously proposed a Cole-Cole form for susceptibilities that accounted for dynamics observed over a similar lengthscale and time scale in optical Kerr effect data. 61 We note also that, very shortly after the first posting of a portion of this work, 62 Gupta et al 63 also showed that β JG relaxation could be obtained from EINS.…”
Section: Discussionmentioning
confidence: 59%
“…To capture the dynamics of the PEO chains in this confinement, we used Cole-Cole function (Equation 2) to fit S(Q, E) in the energy space. Cole-Cole distribution function has been successfully used to capture the dynamics in various confined systems (Cole and Cole, 1941;Gupta et al, 2016;Mamontov and O'Neill, 2017;Dyatkin et al, 2018). In Cole-Cole function, two parameters are fitted independently: E 0 (Q), the half width at half maximum of S(Q, E), and α(Q), the stretched exponential.…”
Section: Resultsmentioning
confidence: 99%
“…To further investigate the dynamical mechanisms behind ice nucleation in GO aqueous dispersions, we performed QENS experiments on GOs in H 2 O and D 2 O, as well as pure water, above and approaching the ice formation temperature. QENS has proved to be a prevailing tool to study the dynamics of water molecules on the timescale of pico- to nano-seconds, 27 since the hydrogen atoms have much larger incoherent scattering cross section compared to other atoms present in the GO aqueous dispersions. The normalized QENS spectra from IRIS are shown in Figs.…”
Section: Resultsmentioning
confidence: 99%
“…The stretch exponent β can be considered as Q-independent in the Q range of measurements and can be obtained by fitting curves at all 10 Q values together. 27 …”
Section: Resultsmentioning
confidence: 99%